New insights into burnout and health care: Strategies for improving civility and alleviating burnout. (1st February 2017) - Maslach, Christina; Leiter, Michael P.
Abstract: What do we know about burnout, and what can we do about it? This article will provide an overview of what has been learned from current research on burnout, and what are the implications of the key themes that have emerged. One theme involves the critical significance of the social environment in health care settings. A second theme is the challenge of how to take what we know, and apply it to what we can do about burnout. What we need are new ideas about potential interventions, and clear evidence of their effectiveness. One example of this perspective addresses burnout by improving the balance of civil, respectful social encounters occurring during a workday. Research has demonstrated that not only can civility be increased at work but that doing so leads to an enduring reduction in burnout among health care providers. Lessons learned from this extensive research form the basis of recommendations for medical education. Specifically, the effectiveness of both the academic content and supervised practice would be enhanced by giving a greater emphasis to the social dynamics of healthcare teams. This perspective can help new physicians in avoiding potential pitfalls and recovering from unavoidable strains.